Cumulative Evidence for Associations Between Genetic Variants in Interleukin 6 Receptor Gene and Human Diseases and Phenotypes - Zhang, Min; Bai, Ye; Wang, Yutong; Cui, Huijie; Tang, Mingshuang; Wang, Lanbing; Wang, Xin; Gu, Dongqing (Frontiers in Immunology, 2022)
Background: Genetic studies have linked polymorphisms in the interleukin 6 receptor (IL6R) gene to the risk of multiple human diseases and phenotypes, yet have reported inconsistent results. We aimed to synthesize current knowledge of variants in the IL6R gene on the risk of diseases and phenotypes. Methods: We searched the Medline and Embase databases to identify relevant publications. Meta-analysis was performed utilizing DerSimonian and Laird random-effects model. We also graded cumulative evidence for significant associations. Furthermore, phenome-wide analyses and functional annotations were performed for variants with strong evidence. Results: We included 155 studies for evaluating the associations between 80 polymorphisms in the IL6R gene and the risk of 102 human diseases and 98 phenotypes. We conducted 58 main meta-analyses, and 41 significant associations were identified. Strong evidence was assigned to 29 associations that investigated ten variants (rs2228145, rs4129267, rs7529229, rs4537545, rs7518199, rs4845625, rs4553185, rs4845618, rs4845371, and rs6667434) related to the risk of four cardiovascular diseases (coronary heart disease, coronary artery disease, atherosclerosis, abdominal aortic aneurysms), four inflammatory diseases (rheumatoid arthritis, Crohn’s disease, dermatitis, asthma) and concentration of four phenotypes (C-reactive protein, fibrinogen, IL-6, and sIL-6R). Furthermore, phenome-wide analysis verified rs2228145 associated with asthma and dermatitis risk. Functional analyses indicated that these polymorphisms fall within exon, enhancer regions. Conclusions: Our study comprehensively summarizes current data on the genetic architecture of the IL6R gene and highlights the pharmacological targeting potential of IL-6R on cardiovascular and inflammatory diseases.